2019
DOI: 10.4236/msce.2019.711004
|View full text |Cite
|
Sign up to set email alerts
|

Risk level Assessment of the Desalter and Preflash Column of a Nigerian Crude Distillation Unit

Abstract: A study of operability and assessment of the safety level of a crude distillation unit in a Nigerian refinery has been carried out. In a crude distillation unit of a refinery, the desalter and preflash column, as well as their associated pipe works and pumps, are considered to have high-risk factors that can present operability problems and possibly hazardous conditions. Applying the HAZOP methodology, a total of 25 guide words were suitably applied on 4 nodes to study the possible deviations that may occur. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…As a consequence, the fracture of the line, oil spill, risk of fire and release of H 2 S. To mitigate the possible problems, H 2 S alarm and fire alarm were proposed to safeguard the installation of the PSV [16]. For Kletz [26] and Cozzani [27], these deviations may be caused by a failure in the pressure valve manometer, failure of the pressure sensors, error in the safety circuit or calibration error of the manometers. As a safeguard, it is suggested to install a pressure control valve, installation of pressure alarms, periodic inspections and maintenance of valves and sensors [18,28].…”
Section: Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the fracture of the line, oil spill, risk of fire and release of H 2 S. To mitigate the possible problems, H 2 S alarm and fire alarm were proposed to safeguard the installation of the PSV [16]. For Kletz [26] and Cozzani [27], these deviations may be caused by a failure in the pressure valve manometer, failure of the pressure sensors, error in the safety circuit or calibration error of the manometers. As a safeguard, it is suggested to install a pressure control valve, installation of pressure alarms, periodic inspections and maintenance of valves and sensors [18,28].…”
Section: Pressurementioning
confidence: 99%
“…Benedetti-Marquez [10] and Cozzani [27] stated that these operational errors cause line clogging, delay in starting, economic loss, damage to the pump, heating and/or decomposition of the oil into lighter fractions that can lead to the explosion. To minimise these risks, Kletz [26] and Orugba [30] recommend inserting protections such as low flow alarm, as well as turning off the suction pump if low amperage, low vibration, high temperature or low/high pressure are detected in the pump discharge.…”
Section: Starting or Stoppingmentioning
confidence: 99%
“…Furthermore, faecal sludge contains a large amount of organic matter, which causes offensive odour during the degradation process and further worsens the environmental condition. Faecal sludge also generates a high volume of greenhouse gases (GHGs), which have a harsh impact on the environment and the natural ecosystem [17][18]. Nsiah-Gyambibi et al [19] reported that the disposal of untreated faecal sludge into the environment generates about 40% of the total GHGs.…”
Section: Introductionmentioning
confidence: 99%
“…For a SIPROD mode, a unique engineering design modification needs to be performed on the SIPROD platform to accommodate the rig [18,19]. It ensures that all safety and production systems are upgraded to manage the risks due to simultaneous activities on the platform [7,20]. As in the article by Diego [21], a SIMOP risk assessment is conducted during commissioning at a new petrochemical plant in numbers of the workshop, attended by multidisciplinary participants to ensure all risks are appropriately managed concerning 2-phases activities.…”
Section: Introductionmentioning
confidence: 99%